Groundwater response to climate variability in Mediterranean type climate zones with comparisons of California (USA) and Portugal - Malmgren, Katherine (2022)
Aquifers are a fundamental source of freshwater, yet they are particularly vulnerable in coastal regions with Mediterranean type climate, due to both climatic and anthropogenic pressures. This comparative study examines the interrelationships between ocean-atmosphere teleconnections, groundwater levels and precipitation in coastal aquifers of California (USA) and Portugal. Piezometric and climate indices (1989-2019) are analyzed using singular spectral analysis and wavelet transform methods. Singular spectral analysis identifies signals consistent with the six dominant climate patterns: the Pacific Decadal Oscillation (PDO), the El Nino-Southern Oscillation (ENSO), and the Pacific/North American Oscillation (PNA) in California, and the North Atlantic Oscillation (NAO), the Eastern Atlantic Oscillation (EA) and the Scandinavian Pattern (SCAND) in Portugal. Lower-frequency oscillations have a greater influence on hydrologic patterns, with PDO (52.75%) and NAO (46.25%) on average accounting for the largest amount of groundwater level variability. Wavelet coherences show nonstationary covariability between climate patterns and groundwater levels in distinct period bands: 4-8 years for PDO, 2-4 years for ENSO, 1-2 years for PNA, 5-8 years for NAO, 2-4 years for EA and 2-8 years for SCAND. Wavelet coherence patterns also show that coupled climate patterns (NAO+ EA- and paired PDO and ENSO phases) are associated with major drought periods in both the Mediterranean climate zones.